Elevated expression of type II Na+ channels in hypomyelinated axons of shiverer mouse brain - Westenbroek, RE (J Neurosci, 1992)
Type I and type III Na+ channels are localized mainly in neuronal cell bodies in mouse brain. Type II channels are preferentially localized in unmyelinated fiber tracts but are not detectable in normally myelinated fibers. In shiverer mice, which lack compact myelin due to a defect in the myelin basic protein gene, elevated expression of type II Na+ channels was observed in the hypomyelinated axons of large-caliber fiber tracts such as the corpus callosum, internal capsule, fimbria, fornix, corpus medullare of the cerebellum, and nigrostriatal pathway by immunocytochemical analysis with subtype-specific antibodies. No difference was observed in the localization of type I and type III Na+ channels between wild-type and shiverer mice. These findings support the hypothesis that type II Na+ channels are preferentially localized in axons of brain neurons and suggest that their density and localization are regulated by myelination. The selective increase in the number of type II channels in hypomyelinated fiber tracts may contribute to the hyperexcitable phenotype of the shiverer mouse.